2003
DOI: 10.1136/bjo.87.3.266
|View full text |Cite
|
Sign up to set email alerts
|

Sutureless cataract surgery with nucleus extraction: outcome of a prospective study in Nepal

Abstract: Aim: To report the short and medium term outcome of a prospective series of sutureless manual extracapsular cataract extractions (ECCE) at a high volume surgical centre in Nepal. Methods: Cataract surgery was carried out, on eyes with no co-existing diseases, in 500 consecutive patients who were likely to return for follow up. The technique involved sclerocorneal tunnel, capsulotomy, hydrodissection, nucleus extraction with a bent needle tip hook, and posterior chamber intraocular lens (PC-IOL) implantation ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
4
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(85 citation statements)
references
References 15 publications
6
70
4
5
Order By: Relevance
“…Hennig and co-authors 16 reported posterior capsular rent in 0.2% cases whereas Khan reported 3.33% 17 .…”
Section: Posterior Capsular Rentmentioning
confidence: 91%
See 1 more Smart Citation
“…Hennig and co-authors 16 reported posterior capsular rent in 0.2% cases whereas Khan reported 3.33% 17 .…”
Section: Posterior Capsular Rentmentioning
confidence: 91%
“…Similarly, Hennig et al 16 in their study reported a BCVA of 6/18 or better in 96.2% and 88.3% respectively.…”
Section: Visual Outcomementioning
confidence: 99%
“…The cost of these can be reduced to less than d5 through local manufacture and bulk purchase. 11 In most communities, patients are willing to pay the equivalent of 1 month's wages for a cataract operation. 12 This should be the average price for cataract surgery.…”
Section: Costmentioning
confidence: 99%
“…Using this system, the median surgical time (time required by the ophthalmologist) per case can be reduced to less than 5 min. 11 In order to maximise surgical output, the time between surgeries must be reduced, as well as operating time. If…”
Section: Personnelmentioning
confidence: 99%
See 1 more Smart Citation